Energy Harvesting Based on a Novel Piezoelectric 0.7PbZn0.3Ti0.7O3-0.3Na2TiO3 Nanogenerator - Radeef, Z.S.; Chong, W.T.; Ong, Z.C.; Khoo, S.Y. (MDPI, 2017)
Recently, piezoelectric materials have achieved remarkable attention for charging wireless sensor nodes. Among piezoelectric materials, non-ferroelectric materials are more cost effective because they can be prepared without a polarization process. In this study, a non-ferroelectric nanogenerator was manufactured from 0.7PbZn0.3Ti0.7O3-0.3Na2TiO3 (PZnT-NT). It was demonstrated that the increment of conductivity via adding the Na2TiO3 plays an essential role in increasing the permittivity of the non-ferroelectric nanogenerator and hence improved the generated power density. The dielectric measurements of this material demonstrated high conductivity that quenched the polarization phase. The performance of the device was studied experimentally over a cantilever test rig; the vibrating cantilever (0.4 ms-2) was excited by a motor operated at 30 Hz. The generated power successfully illuminated a light emitting diode (LED). The PZnT-NT nanogenerator produced a volume power density of 0.10 μw/mm3 and a surface power density of 10 μw/cm2. The performance of the proposed device with a size of (20 × 15 × 1 mm3) was higher in terms of power output than that of the commercial microfiber composite (MFC) (80 × 57 × 0.335 mm3) and piezoelectric bimorph device (70 × 50 × 0.7 mm3). Compared to other existing ferroelectric and non-ferroelectric nanogenerators, the proposed device demonstrated great performance in harvesting the energy at low acceleration and in a low frequency environment.